Intraocular eyelash in anterior chamber following penetrating trauma and self-sealing corneal laceration: Case report - Mohsen Pourazizi; Sepehr Karbasi; Elham Rahmanipour (Trauma Case Reports)
Background: Intraocular foreign bodies pose a significant clinical challenge. The occurrence of an eyelash within the anterior chamber is infrequent, as illustrated by this case. We present a rare case of two eyelashes inside the anterior chamber following penetrating trauma, a scenario with few documented occurrences, especially those not related to surgical interventions. Case description: A 35-year-old male presented with symptoms of a foreign body sensation, redness, blurred vision, and photophobia two days after sustaining a wire-induced injury. Examination revealed a self-sealing corneal laceration, two eyelashes in the anterior chamber, iridocorneal adhesion, and an irregular iris. The surgical removal of the eyelashes was successfully performed. Postoperatively, the patient's visual acuity improved significantly from 20/50 to 20/20, accompanied by a marked reduction in anterior chamber inflammation. Conclusion: This case highlights the importance of considering all types of intraocular foreign bodies, including seemingly innocuous materials like eyelashes, to diagnose ocular traumas. It highlights the critical need for prompt diagnosis and intervention to prevent long-term complications and ensure favorable outcomes.